Organic positioning strategies and digital consumer behavior: A study in Peru’s real estate sector - Socrates Deza-De-Souza-Ferreyra; Maria Jeanett Ramos-Cavero; Franklin Cordova-Buiza (Innovative Marketing)
This study examined the relationship between organic positioning strategies and the behavior of digital consumers in real estate companies in Peru, a topic of growing importance given the expanding role of digital marketing in the real estate sector. The primary objective was to determine the effectiveness of SEO strategies in influencing consumer behavior. A quantitative methodology was adopted, employing a non-experimental, cross-sectional, and correlational design. 100 real estate SEO experts in Peru, who were recruited from LinkedIn, were surveyed. Data were collected through surveys, and the analysis was conducted using the SPSS statistical software. The findings revealed that brand awareness, keyword analysis, and marketing strategy are pivotal components in the development of successful SEO approaches. Simultaneously, factors such as brand awareness, marketing performance, and brand interaction emerged as critical influencers of digital consumer behavior. The statistical analysis yielded a Pearson correlation coefficient of 0.707, indicating a strong positive relationship between organic positioning strategies and digital consumer behavior. These results underscore the practical value of implementing effective SEO strategies in enhancing consumer engagement and behavior in the digital space. In conclusion, the study demonstrates that well-executed organic positioning strategies can significantly improve digital consumer behavior, offering valuable insights for real estate companies seeking to optimize their digital marketing efforts. This highlights the importance of incorporating targeted SEO techniques to strengthen brand presence and drive consumer engagement in an increasingly competitive market.